Considering Tyler’s Curriculum Model in Health and Physical Education (Journal of Education and Educational Development, 2020)
Tyler’s objectives curriculum model has been a strong influence in the field of curriculum development since its publication in 1949. The influence of this model remains strong despite its age, demonstrating the importance of the questions Tyler based his model around. This discussion paper examines Tyler’s (1949) objectives curriculum model; particularly its advantages and disadvantages and its current relevance. This analysis will occur with the context of health and physical education subject area.